2017
DOI: 10.1021/acs.jnatprod.6b01177
|View full text |Cite
|
Sign up to set email alerts
|

Neomacrophorin X, a [4.4.3]Propellane-Type Meroterpenoid from Trichoderma sp. 1212-03

Abstract: Neomacrophorin X (1) was isolated from Trichoderma sp. 1212-03. Heteronuclear multiple bond correlation (HMBC) spectral analysis indicated a unique [4.4.3]propellane framework, which was verified by the H andC chemical shift calculations based on density functional theory (DFT) and subsequent comparison with experimental data obtained in CDCl. The DFT-based electronic circular dichroism (ECD) calculations were effective in not only determining the absolute configuration but also confirming the relative structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…We compared the experimental ECD spectra of 1 , 10 , and 11 with those obtained by the TD-DFT calculations. A density functional BHLYP/def2-TZVP model under vacuum conditions was selected in these calculations . Calculated ECD spectra were obtained after correction based on the Boltzmann distribution of the conformers.…”
Section: Results and Discussionmentioning
confidence: 64%
“…We compared the experimental ECD spectra of 1 , 10 , and 11 with those obtained by the TD-DFT calculations. A density functional BHLYP/def2-TZVP model under vacuum conditions was selected in these calculations . Calculated ECD spectra were obtained after correction based on the Boltzmann distribution of the conformers.…”
Section: Results and Discussionmentioning
confidence: 64%
“…Thermoactinoamide A (Teta et al, 2017) Trichoderma sp. Neomacrophorin X (Kusakabe et al, 2017) more plants species are described, the more diversity is to be found in the end-products of these pathways along with possibly valuable "new" compounds. A recent interesting study (Henz Ryen and Backlund, 2019) discussed the chemical Angiosperms' diversity among natural products and some of these evolutionary mechanisms leading to diversification of chemical structures in function of the group of secondary metabolites (flavonoids, tropane alkaloids, sesquiterpene lactones, and betalains).…”
Section: Thermoactinomyces Vulgarismentioning
confidence: 99%
“…HL60 cells (RCB0041, RIKEN BioResource Center, Tsukuba, Japan) were grown in RPMI 1640 medium supplemented with 10% heat-inactivated FBS (Biowest SAS, Nuaillé, France) and penicillin (50 units/mL)-streptomycin (50 µg/mL) (Gibco Corp., Carlsbad, CA, USA) in a humidified atmosphere at 37 °C under 5% CO 2 . Cytotoxicity of FAs against HL60 cells was assayed by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) (Dojindo Lab., Kumamoto, Japan) method as described previously [28]. Camptothecin was used as a positive control for HL60 cells with an IC 50 value of 23.6 nM.…”
Section: Methodsmentioning
confidence: 99%